2005
DOI: 10.1248/jhs.51.62
|View full text |Cite
|
Sign up to set email alerts
|

17.BETA.-Estradiol Primes Elicitation of Inducible Nitric Oxide Synthase Expression by Lipopolysaccharide and Interferon-.GAMMA. in Mouse Macrophage Cell Line J774.1

Abstract: The effects of estrogenic compounds on nitric oxide (NO) production by macrophages were examined. 17β-Estradiol promoted NO production triggered by lipopolysaccharide (LPS) and/or interferon (IFN)-γ in the mouse macrophage cell line J774.1. Other estrogen-like substances such as estrone, 17α-ethynylestradiol and bisphenol A also enhanced NO synthesis, but this NO synthesis was not activated by Ca 2+ ionophore A23187. RT-PCR analysis demonstrated induction of inducible nitric oxide synthase (iNOS) mRNA in J774.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…E2 enhanced auricle edema at 6 h after elicitation, and showed a tendency to enhance edema at 24 h when compared to vehicle-treated mice. The increase in IFN-γ expression at 6 h coincided with the increase in auricle swelling at 6 h. E2 failed to promote swelling at 24 h, enhanced IL-10 expression at 24 h, and suppressed the IFN-γ effect at 48 h. We have reported that E2 enhances iNOS expression in the mouse macrophage J774.1 cell line [14]. In the present study, it was expected that macrophage activity would be augmented directly by E2, or indirectly via the E2-induced increase in IFN-γ.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…E2 enhanced auricle edema at 6 h after elicitation, and showed a tendency to enhance edema at 24 h when compared to vehicle-treated mice. The increase in IFN-γ expression at 6 h coincided with the increase in auricle swelling at 6 h. E2 failed to promote swelling at 24 h, enhanced IL-10 expression at 24 h, and suppressed the IFN-γ effect at 48 h. We have reported that E2 enhances iNOS expression in the mouse macrophage J774.1 cell line [14]. In the present study, it was expected that macrophage activity would be augmented directly by E2, or indirectly via the E2-induced increase in IFN-γ.…”
Section: Discussionmentioning
confidence: 66%
“…Vascular dilation is also induced by inflammatory cytokines such as IFN-γ, tumor necrosis factor (TNF)-α, and interleukin (IL)-1β [12,13]. We have previously reported that E2 enhanced inducible nitric oxide synthase (iNOS) in the mouse macrophage cell line J774.1, and that E2 enhanced IFN-γ in mouse CHS [9,14]. These data suggest that E2, both directly and indirectly, enhances iNOS expression to dilate vascular vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the actions of 17␤-estradiol on macrophages. Such studies confirm a mechanistic role for high-affinity estrogen receptors, but yield conflicting reports as to the effects of 17␤-estradiol on cell function, ranging from inhibition to promotion of activation (compare, for example, findings reported by Hayashi et al, 1998;Lu et al, 2004;Vegeto et al, 2004;Sakazaki et al, 2005). On the other hand, little attention has been given to the effects of 17␤-estradiol metabolites, such as 2MEO, on macrophage function.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen receptor-␤ agonists have attracted attention as potential anti-inflammatory agents (Koehler et al, 2005). Previous studies in LPS/IFN␥-stimulated J774 cells found in one case modest suppression of nitric-oxide production by 17␤-estradiol (Hayashi et al, 1998) and in another case enhancement (Sakazaki et al, 2005), but did not examine other inflammatory mediators. However, in the present study concentrations of 17␤-estradiol far greater than those required to saturate high-affinity estrogen receptors had no effect on J774 macrophage activation.…”
mentioning
confidence: 99%